A Self-Constraint Underwater Positioning Method without the Assistance of Measured Sound Velocity Profile. Issue 1 (2nd January 2023) - Zhao, Jianhu; Liang, Wenbiao; Ma, Jinye; Liu, Meiqin; Li, Yuqing
Abstract: Aiming at the problem that lack of the measured sound velocity profile (SVP) leads to the unreliable underwater positioning solution, this paper proposed an efficient underwater positioning method by the self-constraint conditions of water depth and sound velocity gradient. To construct the depth constraint condition, the sound propagation distance error model is deduced by acoustic ray tracing, and the sound vertical propagation error model related to the incident angle and sound velocity error is given firstly. By fitting the vertical propagation error model, the reference depth is solved, and the vertical propagation distances between the transducer and the underwater control points of all observation epochs are gotten. Then with the solved vertical distance of each epoch and the sound velocity gradient from neighbor SVPs as the constraint conditions, the SVP is retrieved by the simulated annealing (SA) algorithm. With the retrieved SVP, the underwater positioning can be performed when the measured SVP is absent. The proposed method was verified by an experiment in the 3000 m depth water area of the South China Sea. The results achieved 2.07 m/s of standard deviation of the SVP inversion, centimeter-level horizontal positioning accuracy and 0.54 m of vertical positioning accuracy under the circumstance of lack of SVP measurement.